Insight of PrEP and Testing STI Puzzle - Nurwestu Rusetiyanti (Academic Hospital Journal, 2021)
Pre Exposure Prophylaxis (PrEP) is the use of Anti Retroviral (ARV) drugs by HIV-uninfected people to block the acquisition of HIV before exposure to HIV. There are concerns that PrEP introduction and scale up may pose risks, such as sexual behavior change in specific populations, and have an impact on the budget in already constrained health systems. Therefore, public health measures for the prevention of HIV and other STIs need to be enhanced, such as the prioritization of PrEP, coupled with more effective STI screening and treatment. Integration of STI and PrEP programmes can be viewed bi-directionally (not only integrating STI services into PrEP services but also considering STI clients as people also at risk for HIV and therefore potentially eligible for PrEP). This approach fosters synergies and efficiencies from a public health perspective. However, there are many challenges to programmatic integration, including siloed funding streams and programmes, the availability and costs of expanded etiological STI testing, and gaps in capacity and training for STI management. Keywords : PrEP, STI, services